Association of salt sensitivity in rats with genes of the major histocompatibility complex - Kunes, J; Zicha, J (Hypertension (Dallas, Tex., 1994)
Dietary sodium intake has long been considered an important factor in the genesis and maintenance of hypertension in both humans and experimental animals. To identify the possible association between salt sensitivity and genes of the major histocompatibility complex (RT1 complex), we studied the blood pressure response to an 8% NaCl diet in normotensive Lewis rats, spontaneously hypertensive rats (SHR), and Lewis.1K congenic rats (congenic to Lewis with the SHR main histocompatibility complex RT1). During the first 4 weeks of a high salt diet, the blood pressure increase was the same in SHR and Lewis.1K congenic rats. Thus, the presence of a small segment of SHR chromosome 20 with genes of the RT1 complex (and closely related genes) in the Lewis genome sensitized the blood pressure of these animals to the hypertensive effects of a high salt diet. Genes of the RT1 complex influenced the salt-induced increase of relative kidney weight more than that of relative heart weight. Our results support the hypothesis that some alleles within or close to the RT1 complex might be responsible for the higher sensitivity of hypertensive individuals to certain environmental stressors, including high salt intake.
Keywords: velikost orgánu; Drug Resistance; Male; Organ Size; Sodium Chloride; srdce; potkani inbrední SHR; Kidney; mužské pohlaví; hlavní histokompatibilní komplex; léková rezistence; chlorid sodný; geny; Genes; dieta s nízkým obsahem soli; krysa rodu Rattus; Diet, Sodium-Restricted; Animals; krevní tlak; ledviny; zvířata; Rats, Inbred Lew; Rats; Blood Pressure; Rats, Inbred SHR; potkani inbrední LEW; Heart; Major Histocompatibility Complex